The current educational interventions for teaching and learning evidence-based practice knowledge, skills, attitudes, and behaviours: a systematic review among undergraduate healthcare students in developing countries - Nalweyiso, Dorothy Irene; Mbabazi, Johnson; Josette, Bettany Saltikov; Kabanda, Joseph; Jeff, Breckon; Nnyanzi, Lawrence Achilles; Kawooya, Michael Grace; Mubuuke, Aloysius Gonzaga; Kinengyere, Alison Annet; Katherine, Sanderson (Cogent Education, 2025)
This study aims to evaluate the current educational interventions designed to teach evidence-based practice (EBP) knowledge, skills, attitudes, and behaviours among undergraduate healthcare students in developing countries. A systematic review of quantitative primary research studies was conducted. From an initial set of 942 studies, 848 were screened based on their titles and abstracts, and 11 full-text articles were assessed. After applying exclusion criteria, eight studies were included in the review. These studies were identified through a comprehensive search of electronic databases, including CINAHL, MEDLINE, EMBASE, PUBMED, and ERIC. Two independent reviewers screened, appraised, and extracted data, utilizing the McMaster appraisal tools to assess methodological quality. A best-evidence synthesis approach was applied to summarize the findings in accordance with PRISMA guidelines. The review identified eight studies, 87.5% of which were conducted in Asian countries. The majority (62.5%) of these studies employed survey designs, and 75% incorporated blended teaching methods to deliver EBP content. A notable finding was the absence of EBP-focused interventions for healthcare students in sub-Saharan Africa. There is a significant gap in research regarding educational interventions for teaching EBP to undergraduate healthcare students in developing countries. The findings suggest a need for more targeted research and interventions, particularly in regions like sub-Saharan Africa.